2011
DOI: 10.4049/jimmunol.1101834
|View full text |Cite
|
Sign up to set email alerts
|

Immune Regulation through Mitochondrion-Dependent Dendritic Cell Death Induced by T Regulatory Cells

Abstract: Dendritic cells (DCs) harbor an active mitochondrion-dependent cell death pathway regulated by Bcl-2 family members and undergo rapid turnover in vivo. However, the functions for mitochondrion-dependent cell death of DCs in immune regulation remain to be elucidated. Here we show that DC-specific knockout of pro-apoptotic Bcl-2 family members, Bax and Bak, induced spontaneous T cell activation and autoimmunity in mice. In addition to a defect in spontaneous cell death, Bax−/−Bak−/− DCs were resistant to killing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 78 publications
0
15
0
Order By: Relevance
“…Paradoxically, it was also suggested that impaired apoptosis of DCs might increase DC numbers and cause autoimmunity 3739 . However, it remains unclear whether the in vivo blockade of apoptosis was limited to DCs in these studies; indeed, some of these studies used a Cre-deleter strain that has a broad deletion range (BOX 1).…”
Section: The Role Of Dcs In Autoimmunity: General Aspectsmentioning
confidence: 99%
“…Paradoxically, it was also suggested that impaired apoptosis of DCs might increase DC numbers and cause autoimmunity 3739 . However, it remains unclear whether the in vivo blockade of apoptosis was limited to DCs in these studies; indeed, some of these studies used a Cre-deleter strain that has a broad deletion range (BOX 1).…”
Section: The Role Of Dcs In Autoimmunity: General Aspectsmentioning
confidence: 99%
“…On the other hand, articles published in 2011 demonstrate that T regulatory cells are controlled by the apoptosis of dendritic cells [208] and by caspase processed cytokines [189]. Furthermore, T regulatory cells control the onset and perpetuation of autoimmunity acting on Th2 cells [207], through the expression of CD103 [197], and on CD8+ cytotoxic cells [196].…”
Section: T Cell Subpopulationsmentioning
confidence: 96%
“…Treg cells in tumor tissues have also been reported to kill DCs in a perforin-dependent manner (74). We have found that activated Treg cells could directly induce cell death in DCs in a Bax and Bak–dependent manner to inhibit DC-dependent immune responses (84). Therefore, Treg-mediated killing of DCs could provide an alternative mechanism for immunosuppression by Treg cells (Fig.…”
Section: Treg Cells On DC Survivalmentioning
confidence: 99%
“…We observed a small but reproducible increase of CD4 + FoxP3 + Treg cells in autoimmune mice harboring apoptosis deficiency in DCs (1). We have also identified that deficiencies in Bax and Bak enable DC to be resistant to killing by Treg cells to over-activate T effector cells (84). However, other mechanisms by which apoptosis-deficient DCs overcome the inhibition by Treg cells to over-activate T effector cells remain to be elucidated.…”
Section: Treg Cells On DC Survivalmentioning
confidence: 99%
See 1 more Smart Citation